2012
DOI: 10.1161/atvbaha.112.245696
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression and Genetic Variation of Lmf1 Affect LPL Activity in Mice and Humans

Abstract: Objective Lipoprotein lipase (LPL) is a principal enzyme in lipoprotein metabolism, tissue lipid utilization and energy metabolism. LPL is synthesized by parenchymal cells in adipose, heart and muscle tissues followed by secretion to extracellular sites, where lipolyic function is exerted. The catalytic activity of LPL is attained during post-translational maturation, which involves glycosylation, folding and subunit assembly within the endoplasmic reticulum (ER). A lipase-chaperone, lipase maturation factor 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…, Hosseini et al . ), we wished to extend our previous findings by assessing the depot specificity of action of chronic PPAR γ activation at the levels of LPL mass/specific activity, and recently characterized, major modulators of LPL action. In SF of fasted animals, the induction of LPL activity by PPAR γ activation was of higher magnitude than that of its mass, which is suggestive of a positive post‐translational regulation of LPL.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, Hosseini et al . ), we wished to extend our previous findings by assessing the depot specificity of action of chronic PPAR γ activation at the levels of LPL mass/specific activity, and recently characterized, major modulators of LPL action. In SF of fasted animals, the induction of LPL activity by PPAR γ activation was of higher magnitude than that of its mass, which is suggestive of a positive post‐translational regulation of LPL.…”
Section: Discussionmentioning
confidence: 97%
“…, Hosseini et al . ). Whereas lipase maturation factor 1 (LMF1) and glycosylphosphatidylinositol‐anchored HDL‐binding protein 1 (GPIHBP1) increase LPL activity by, respectively, coordinating the proper folding of LPL into its active form and its transport from the adipocyte to the capillary endothelium where TG is hydrolysed, angiopoietin‐like protein 4 (ANGPTL4) catalyses a conformational switch from active LPL dimers to catalytically inactive monomers (Sukonina et al .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A similar observation was made by Levak-Frank et al (32), who found that increasing muscle LPL expression increased HDL turnover. It will be interesting to explore the mechanism in the future in the Adipoq-LPL model because there have been different reports of the effect of increasing LPL on HDL in other models, with some models of LPL overexpression having no change in HDL (31,33,34) and one model reporting an increase in HDL (35).…”
Section: Discussionmentioning
confidence: 99%
“…Canonical signaling through Ire1␣ affects lipogenesis and very low-density lipoprotein (VLDL) secretion (42)(43)(44), whereas non-canonical UPR signaling involving the cAMP response element-binding protein, hepatocyte-specific regulates lipolysis through the transcriptional regulation of apolipoproteins that activate or inhibit lipoprotein lipase activity (45). As Lmf1 overexpression results in elevated tissue lipoprotein lipase activity (46), UPR-induced Lmf1 expression may represent a novel mechanism through which ER stress modulates lipolysis and tissue lipid uptake. However, our study demonstrates that ER stress-induced Lmf1 regulation also occurs in a lipase-independent cellular context.…”
Section: Discussionmentioning
confidence: 99%